Probability - Boumaraf Badreddine (university of Souk Ahras, 2025)
This module provides a rigorous foundation in modern probability theory, moving from an intuitive understanding to a formal mathematical framework. Students will transition from the study of discrete probability spaces to continuous models, mastering key concepts such as random variables, probability distributions, expectation, variance, and fundamental limit theorems. The course emphasizes the axiomatic approach, mathematical proofs, and the application of measure-theoretic concepts, preparing students for advanced study in statistics, stochastic processes, and applied mathematics.